Contribution of non-exchangeable K in soils from Southern Brazil under potassium fertilization and successive cropping - Steiner, Fábio; Lana, Maria (Revista Ciência Agronômica, 2018)
Intense cropping of plants in pots was used to assess the contribution of non-exchangeable K to plant uptake in different soils of Paraná State, Brazil. Surface samples from nine soil types were fertilized or not with K fertilizer and subjected to six successive cropping (i.e., soybean, pearl millet, wheat, common beans, soybean and maize) under greenhouse conditions. The crops were grown in 8-L pots for 45 days, and at the end of the sixth cropping, the soil was sampled to determination non-exchangeable and exchangeable K. Shoot dry matter yield, K taken up, non-exchangeable pool contribution to K nutrition of plants were also determined. Soils differ in the ability to K supply to the plants in the short to medium term, due to the wide range of parent material and exchangeable K and non-exchangeable K pools. When the soils were not fertilized with K, the successive cropping of plants resulted in a continuous process of depletion of non-exchangeable K and exchangeable K pools; however, this depletion was less pronounced in soils with higher potential buffer capacity of K. Concentrations of non-exchangeable K and exchangeable K were increased with the addition of K fertilizers, indicating the occurrence of K fixation in soil. Non-exchangeable K contribution to K nutrition of plants during the six croppings ranged from 50 to 73% and from 1 to 18%, respectively, without and with K fertilizer addition. These data report the importance of non-exchangeable K pools in the supply of this nutrient to plants in agricultural production systems.